The effects of aminoguanidine on serum paraoxanase activity in streptozotocin-induced diabetic rats - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2011)
Aim: Diabetes is a systemic disease with increased oxidative damage, lipid oxidation and decreased prevention of LDL oxidation. Some of the preventive effects of HDL is thought to be mediated by paraoxanase. Paraoxonase activity is reduced in diabetes. Aminoguanidine, inhibits the formation of advanced glycation endproducts by reacting with intermediate products of glycation. We aimed to investigate the effects of the inhibition of advanced glycation by aminoguanidine on paraoxonase activity in a diabetes model. Methods: 32 10-week male Sprague-Dawley rats were divided into four groups; In two groups diabetes was induced with 65mg/kg of intraperitoneal streptozotocin. One of them was followed without further intervention (DM). The other group was given 1 g/L of aminoguanidine ad libitum in drinking water (DM+AG). The third group was followed as healthy controls (HC). Only AG was given to the fourth group (HC+AG). Paraoxonase (PON) activity was determined according to Eckerson's method. Results: Blood glucose and HbA(1c) levels were significantly elevated in DM and DM+AG groups compared to the healthy controls. There was no difference in cholesterol and HDL levels among groups. The triglyceride level of DM+AG group was significantly elevated compared to HC and HC+AG groups. The PON levels were significantly decreased in DM, DM+AG and HC+AG groups compared to healthy controls. PON levels were correlated with HDL levels and inversely correlated with glucose and HbA(1c) levels. Conclusion: The elevation of glucose and HbA(1c) levels in diabetic groups compared to healthy controls showed that the induction of diabetes model was successful. The decrease in PON levels in diabetic groups is consistent with literature. The inverse correlation between PON and glucose and HbA(1c), despite the lack of a difference among HDL levels suggested that the decrease in PON activity could be due to the glycation of the enzyme. The decrease in PON activity in HC+AG group compared to the HC group implied that the effects of aminoguanidine may not be mediated via PON.
Keywords: Diabetes mellitus; streptozotocin; aminoguanidine; paraoxonase; GLYCATION END-PRODUCTS; PARAOXONASE ACTIVITY; OXIDATIVE INACTIVATION; MELLITUS; COMPLICATIONS; AGES; LDL; HDL